Gender differences in anxiety of children of senior preschool age - Oxana Fedorchenko (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2015)
This article contains methodological studies and experience of practical research of gender differences in anxiety of preschool children. The peculiarity and novelty of scientific material consists in the experimental determination of basic psychological factors of anxiety of preschool children during their interpersonal interactions.
Keywords: clinical psychology; anxiety; preschool children; gender differences in anxiety; anxiety of boys; anxiety of girls